Curing composition as well as preparation method and application thereof

Through the use of acrylic prefabricated, acrylic monomers, silicane coupling agents and curetic compositions in printing processes, solve the problem of mesh blocks caused by oxygen blocking, and improve the light use of photovoltaic components Rate.

CN119371609APending Publication Date: 2025-01-28TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531524.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the printing process, the acrylic system is prone to blockage of the mesh plate due to the oxygen resistance problem, and the light transmittance and refractive index of the existing glue are low, which cannot improve the utilization rate of light of photovoltaic modules.

Method used

Provide a solid composition, including acrylic prefabricated, acrylic monomer, siane coupling agent and cause, and the activation of the internet -shaped structure through the free radical polymerization reaction and the activation of the optical cause, which improves CICC and inhibit oxygen blocking.

Benefits of technology

This curing composition has good yellow resistance, abrasion resistance, suitable refractive index and high light transmission rate. It is suitable for the front blue film protection of solar cells, reducing packaging costs and improving light utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371609A_ABST
    Figure CN119371609A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides a curing composition as well as a preparation method and application thereof. The curing composition comprises an acrylate prepolymer, an acrylic monomer, a silane coupling agent and an initiator, and relative to 100 parts by weight of the acrylate prepolymer, the acrylic monomer accounts for 25-40 parts by weight, the silane coupling agent accounts for 0.5-1.5 parts by weight, and the initiator accounts for 1-3 parts by weight. The curing composition provided by the embodiment of the invention has better yellowing resistance, wear resistance, proper refractive index and higher light transmittance, and is moderate in viscosity, so that a screen printing plate is not easy to block in a silk-screen printing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a curing composition and a preparation method and application thereof. Background Art

[0002] In order to avoid the wear of photovoltaic cells during transportation, battery isolation pads are usually used to protect photovoltaic cells. However, conventional battery isolation pads are expensive and have no gain effect on photovoltaic modules. Therefore, in order to reduce costs and increase efficiency, transparent glue is applied to the front of the battery for protection. This not only reduces costs, but also adjusts the coating height and refractive index to achieve the effect of improving efficiency.

[0003] At present, the glue in the electronics industry is mainly divided into two systems: epoxy resin system and acrylate system. However, both have obvious disadvantages. For example, the epoxy resin system is prone to yellowing, and it is easy to have problems such as poor aging resistance and UV resistance when encapsulated in photovoltaic modules. The acrylic system glue can solve the problems existing in the epoxy resin system, but in the printing process, the acrylic system is still prone to stencil clogging due to the problem of oxygen inhibition.

[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention

[0005] The embodiments of the present application provide a curing composition and a preparation method and application thereof to solve or alleviate the above-mentioned problem that the acrylic acid system in the printing process is still prone to stencil clogging due to oxygen inhibition.

[0006] According to a first aspect of an embodiment of the present application, a curing composition is provided, comprising: an acrylate prepolymer, an acrylic monomer, a silane coupling agent and an initiator, wherein relative to 100 parts by weight of the acrylate prepolymer, the acrylic monomer is 25-40 parts by weight, the silane coupling agent is 0.5-1.5 parts by weight, and the initiator is 1-3 parts by weight.

[0007] The curing composition of the embodiment of the present application has good yellowing resistance, wear resistance, suitable refractive index and high light transmittance, and moderate viscosity is not easy to cause screen clogging in the screen printing process. This is because the system improves the curing rate, shortens the curing time, and reduces the oxygen diffused to the surface, thereby achieving the effect of inhibiting oxygen inhibition. The curing composition is particularly suitable for the front blue film protection of solar cells, and effectively reduces the packaging cost of photovoltaic modules while improving light utilization.

[0008] Acrylate prepolymer, acrylic monomer, silane coupling agent and initiator react with each other through free radical polymerization, and under the activation of the initiator, active free radicals are generated. The active free radicals can trigger the chain growth reaction of the acrylate prepolymer, so that the acrylic monomer generates linear macromolecules, and these linear macromolecules are interconnected to form a cured combination of a cross-linked network structure.

[0009] In addition, relative to 100 parts by weight of the acrylic ester prepolymer, the acrylic monomer is controlled to be 25-40 parts by weight. If the weight of the acrylic monomer is too high, it will lead to excessive monomers in the cured composition, thereby reducing the mechanical properties of the composition; if the weight of the acrylic monomer is too low, the curing rate will be slowed down, resulting in too low strength of the cured composition; the silane coupling agent is controlled to be 0.5-1.5 parts by weight. If the weight of the silane coupling agent is too high, the viscosity of the system will be reduced, thereby making the rheological properties of the cured composition poor; if the weight of the silane coupling agent is too low, the adhesive properties of the cured composition will be poor and the aging properties will be reduced; the initiator is 1-3 parts by weight. If the weight of the initiator is too high or too low, the reaction rate of the curing composition system will be slowed down and the curing time will be extended. Thus, by controlling the acrylic monomer to be 25-40 parts by weight, the silane coupling agent to be 0.5-1.5 parts by weight and the initiator to be 1-3 parts by weight relative to 100 parts by weight of the acrylic ester prepolymer, a curing composition having good yellowing resistance, abrasion resistance, a suitable refractive index and a high light transmittance can be obtained. The composition is particularly suitable for the front blue film protection of solar cells, and can effectively reduce the packaging cost of photovoltaic modules while improving light utilization.

[0010] According to an embodiment of the present application, the curing composition further includes an accelerator and a stabilizer, and relative to 100 parts by weight of the acrylate prepolymer, the accelerator is 0.5-1.5 parts by weight, and the stabilizer is 0.5-1.5 parts by weight. Other additives are added to the curing system to further improve its system performance: for example, a coupling agent is used to improve the interface performance between the inorganic filler and the organic polymer, improve the physical, chemical and mechanical properties of the composite material, an adhesion promoter is added to improve the bonding performance, and a stabilizer is added to improve the aging resistance. In addition, by controlling the accelerator to be 0.5-1.5 parts by weight relative to 100 parts by weight of the acrylic prepolymer, if the weight of the accelerator is too high, the viscosity of the cured composition will be too low and the rheological properties will deteriorate, if the weight of the accelerator is too low, the adhesive properties of the cured composition will deteriorate, and the aging performance will decrease; the stabilizer is 0.5-1.5 parts by weight, if the weight of the stabilizer is too high, the viscosity of the cured composition will be reduced and the rheological properties will deteriorate, if the weight of the stabilizer is too low, the light stability and UV resistance of the cured composition will be poor. Thus, the physical, chemical and mechanical properties of the cured composition are further improved.

[0011] According to an embodiment of the present application, the acrylate prepolymer includes an epoxy acrylate resin oligomer.

[0012] According to an embodiment of the present application, the acrylic monomer includes one or any combination of ethoxyphenol acrylate, ethoxybisphenol A dimethacrylate, o-phenylphenoxyethyl acrylate, 3-ethoxyethyl acrylate, and biphenylmethanol acrylate.

[0013] According to an embodiment of the present application, the initiator includes 1-hydroxycyclohexyl phenyl ketone and / or phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0014] According to an embodiment of the present application, the silane coupling agent includes one or any combination of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0015] According to an embodiment of the present application, the curing composition further includes a filler, and the filler includes one or any combination of silicon dioxide, diatomaceous earth, calcium carbonate, and talc.

[0016] According to an embodiment of the present application, in the curing composition, the filler is 1.5-3 parts by weight relative to 100 parts by weight of the acrylate prepolymer.

[0017] According to an embodiment of the present application, the silica is porous silica, the diameter of the porous silica is 1-5 μm, and the pore size of the porous silica is 0.3-3 μm.

[0018] According to an embodiment of the present application, the viscosity of the curing composition is 120-150 dPa.s.

[0019] According to an embodiment of the present application, the refractive index of the curing composition is 1.54-1.68.

[0020] According to an embodiment of the present application, the light transmittance of the cured composition is at least 92.5%.

[0021] The second aspect of an embodiment of the present application provides a method for preparing the curing composition of the first aspect, comprising the following steps: first mixing and ball-milling an acrylic monomer, a silane coupling agent, an initiator, a promoter and a stabilizer to obtain a mixture; and second mixing the mixture and the acrylic ester prepolymer to obtain a curing composition.

[0022] The method of the embodiment of the present application first obtains a mixture, and then mixes the mixture with an acrylate prepolymer to obtain a cured composition, so that no pressure is required during the curing process, which simplifies the curing process and improves production efficiency. In addition, the cured composition can be fully mixed to better exert its performance.

[0023] According to an embodiment of the present application, the ball milling speed is 1000r / min-1500r / min.

[0024] According to an embodiment of the present application, the ball milling time is 5-10 min.

[0025] According to an embodiment of the present application, the particle size of the mixture is no greater than 15 μm.

[0026] According to an embodiment of the present application, the temperature of the second mixing is 60-100° C., and the time of the second mixing is 5-80 min.

[0027] The second aspect of the embodiment of the present application provides an application of the curing composition of the first aspect, and the application includes the application of the curing composition in the protection of the blue film on the front of the solar cell. The refractive index of the curing composition of the present application is 1.54-1.68, which forms a gradient difference with the refractive index of the photovoltaic film (1.4-1.5) and the refractive index of the silicon nitride layer on the surface of the solar cell (1.8-2.2), and constitutes a light trapping structure to improve the light utilization rate of the photovoltaic module. In addition, the light transmittance of the curing composition is as high as 92.5%, which is much higher than the light transmittance of the existing blue film protection glue. Therefore, the curing composition of the present application is particularly suitable for the protection of the blue film on the front of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.

[0029] Figure 1 It is a structural schematic diagram of the application of the curing composition provided in the embodiment of the present application in the protection of the blue film of the battery cell.

[0030] Description of reference numerals: 1: Adhesive film layer; 2: Cured composition; 3: Battery cell. DETAILED DESCRIPTION

[0031] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.

[0032] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present application, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. When the second element, component, region, layer or part is discussed, it does not indicate that the present application necessarily has the first element, component, region, layer or part.

[0033] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0034] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0035] In the present application, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to an integer in the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints, which is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed in the present application should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows for broadly including quantitative intervals such as percentage intervals, ratio intervals, and ratio intervals.

[0036] Both the epoxy resin system and the acrylate system have obvious disadvantages. For example, the epoxy resin system is prone to yellowing, and when encapsulated in photovoltaic modules, it is easy to have problems such as poor aging resistance and UV resistance. The acrylic system glue can solve the problems of the epoxy resin system, but in the printing process, the acrylic system is still prone to stencil clogging due to the problem of oxygen inhibition, and the acrylic resin system glue has low light transmittance and refractive index, which cannot improve the utilization rate of light in photovoltaic modules.

[0037] According to a first aspect of an embodiment of the present application, a curing composition is provided, which includes an acrylate prepolymer, an acrylic monomer, a silane coupling agent and an initiator. Relative to 100 parts by weight of the acrylate prepolymer, the acrylic monomer is 25-40 parts by weight, the silane coupling agent is 0.5-1.5 parts by weight, and the initiator is 1-3 parts by weight.

[0038] The curing composition of the embodiment of the present application has good yellowing resistance, wear resistance, suitable refractive index and high light transmittance, and moderate viscosity is not easy to cause screen clogging in the screen printing process. This is because the system improves the curing rate, shortens the curing time, and reduces the oxygen diffused to the surface, thereby achieving the effect of inhibiting oxygen inhibition. The curing composition is particularly suitable for the front blue film protection of solar cells, and effectively reduces the packaging cost of photovoltaic modules while improving light utilization.

[0039] Acrylate prepolymer, acrylic monomer, silane coupling agent and initiator react with each other through free radical polymerization, and under the activation of the initiator, active free radicals are generated. The active free radicals can trigger the chain growth reaction of the acrylate prepolymer, so that the acrylic monomer generates linear macromolecules, and these linear macromolecules are interconnected to form a cured combination of a cross-linked network structure.

[0040] In addition, relative to 100 parts by weight of the acrylic ester prepolymer, the acrylic monomer is controlled to be 25-40 parts by weight. If the weight of the acrylic monomer is too high, it will lead to excessive monomers in the cured composition, thereby reducing the mechanical properties of the composition; if the weight of the acrylic monomer is too low, the curing rate will be slowed down, resulting in too low strength of the cured composition; the silane coupling agent is controlled to be 0.5-1.5 parts by weight. If the weight of the silane coupling agent is too high, the viscosity of the system will be reduced, thereby making the rheological properties of the cured composition poor; if the weight of the silane coupling agent is too low, the adhesive properties of the cured composition will be poor and the aging properties will be reduced; the initiator is 1-3 parts by weight. If the weight of the initiator is too high or too low, the reaction rate of the curing composition system will be slowed down and the curing time will be extended. Thus, by controlling the acrylic monomer to be 25-40 parts by weight, the silane coupling agent to be 0.5-1.5 parts by weight, and the initiator to be 1-3 parts by weight relative to 100 parts by weight of the acrylic ester prepolymer, a curing composition having good yellowing resistance, wear resistance, a suitable refractive index and a high light transmittance can be obtained. The composition is particularly suitable for protecting the front blue film of solar cells, and can effectively reduce the packaging cost of photovoltaic modules while improving light utilization.

[0041] In some embodiments, the curing composition further includes an accelerator and a stabilizer, and relative to 100 parts by weight of the acrylate prepolymer, the accelerator is 0.5-1.5 parts by weight, and the stabilizer is 0.5-1.5 parts by weight. Other additives are added to the curing system to further improve its system performance: for example, a coupling agent is used to improve the interface performance between the inorganic filler and the organic polymer, improve the physical, chemical and mechanical properties of the composite material, an adhesion promoter is added to improve the bonding performance, and a stabilizer is added to improve the aging resistance. In addition, by controlling the accelerator to be 0.5-1.5 parts by weight relative to 100 parts by weight of the acrylic prepolymer, if the weight of the accelerator is too high, the viscosity of the cured composition will be too low and the rheological properties will deteriorate, if the weight of the accelerator is too low, the adhesive properties of the cured composition will deteriorate, and the aging performance will decrease; the stabilizer is 0.5-1.5 parts by weight, if the weight of the stabilizer is too high, the viscosity of the cured composition will be reduced and the rheological properties will deteriorate, if the weight of the stabilizer is too low, the light stability and UV resistance of the cured composition will be poor. Thus, the physical, chemical and mechanical properties of the cured composition are further improved.

[0042] In some embodiments, the acrylate prepolymer includes an epoxy acrylate resin oligomer. The epoxy acrylate resin oligomer has good adhesion and strong chemical corrosion resistance, and can improve the anti-aging performance of the cured composition. The acrylate prepolymer can be used in a photocuring process.

[0043] Optionally, the epoxy acrylate resin oligomer includes one or any combination of bisphenol A epoxy acrylate resin, novolac epoxy acrylate resin, and epoxidized oil acrylate.

[0044] In some embodiments, the acrylic monomer is a highly refractive reactive diluent monomer, which can increase the refractive index and light transmittance of the cured product.

[0045] Optionally, the acrylic monomer includes one or any combination of ethoxyphenol acrylate, ethoxybisphenol A dimethacrylate, o-phenylphenoxyethyl acrylate, 3-ethoxyethyl acrylate, and biphenylmethanol acrylate.

[0046] In some embodiments, the initiator is used to absorb radiation energy and initiate polymerization. The initiator can be a cleavage-type photoinitiator or a hydrogen-cleavage-type initiator, which can contribute to the refractive index and light transmittance of the cured composition.

[0047] Alternatively, the initiator comprises 1-hydroxycyclohexylphenyl ketone and / or phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0048] In some embodiments, the silane coupling agent is used to enhance the bonding strength, water resistance, weather resistance and other properties of the cured composition. Optionally, the silane coupling agent includes one or any combination of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0049] In some embodiments, the accelerator is inactive at room temperature and is activated by heating to initiate a reaction to form a curing composition. Examples include: dicyandiamide, hydrazide, imidazole compounds, boron amine complexes that are solid at room temperature; solid dispersed amine adduct-based latent curing accelerators such as reaction products of amine compounds and epoxy compounds (epoxy addition complexes of amines); and microencapsulated curing agents.

[0050] Preferably, the accelerator includes HN1731, HN-1726 or HN-5562 produced by Changzhou Huake Polymer Co., Ltd.

[0051] In some embodiments, the stabilizer may be any of various existing substances capable of improving storage stability, such as one or any combination of liquid borate compounds, aluminum chelates, and barbituric acid.

[0052] Preferably, the stabilizer includes one or any combination of Tinuvin 123, Tinuvin 292 or Tinuvin 622 produced by BASF Group.

[0053] In some embodiments, by adding fillers to the curing composition, the heat resistance, moisture resistance, and especially heat cycle resistance of the bonded part are improved. The reason why the heat cycle resistance is improved by adding fillers is that the linear expansion coefficient of the cured product is reduced, that is, the expansion-contraction of the cured product caused by the thermal cycle is suppressed.

[0054] Optionally, the filler includes one or any combination of silicon dioxide, diatomaceous earth, calcium carbonate, and talc.

[0055] Optionally, the silica is porous silica, the diameter of the porous silica is 1-5 μm, and the pore size of the porous silica is 0.3-3 μm. Porous silica is beneficial to improving the light transmittance of the cured composition, giving the cured composition better optical properties, higher hardness and better adhesion; and the aforementioned particle size range is beneficial to the dispersion of silica in the cured composition.

[0056] In some embodiments, in the curing composition, the filler is 1.5-3 parts by weight relative to 100 parts by weight of the acrylate prepolymer.

[0057] In some embodiments, the viscosity of the curing composition is 120-150 dPa.s, such as 120 dPa.s, 130 dPa.s, 140 dPa.s, 150 dPa.s, etc.

[0058] In some embodiments, the refractive index of the cured composition is in the range of 1.54-1.6, such as 1.54, 1.58, 1.6, etc.

[0059] In some embodiments, the cured composition has a light transmittance of at least 92.5%.

[0060] A second aspect of an embodiment of the present application provides a method for preparing the above-mentioned curing composition, comprising the following steps: first mixing and ball-milling an acrylic monomer, a silane coupling agent, an initiator, a accelerator, and a stabilizer to obtain a mixture; The mixture and the acrylic prepolymer are second mixed to obtain a curing composition.

[0061] The method of the embodiment of the present application first obtains a mixture, and then mixes the mixture with an acrylate prepolymer to obtain a cured composition, so that no pressure is required during the curing process, which simplifies the curing process and improves production efficiency. In addition, the cured composition can be fully mixed to better exert its performance.

[0062] In some embodiments, ball milling can fully mix the acrylic monomer, silane coupling agent, initiator, accelerator and stabilizer to obtain a mixture with a suitable particle size, thereby improving the leveling performance of the curing composition and making it more uniform during curing; Optionally, the speed of the ball mill is 1000-1500 r / min, for example, 1000 r / min, 1200 r / min, 1300 r / min, 1400 r / min, 1500 r / min, etc.

[0063] Optionally, the ball milling time is 5-10 min, such as 5 min, 8 min, 10 min, etc.

[0064] Optionally, the particle size of the mixture is no greater than 15 μm.

[0065] In some embodiments, the temperature of the second mixing process is controlled to allow the mixture and the acrylic prepolymer to be fully mixed to obtain a cured composition.

[0066] Optionally, the temperature of the second mixing is 60-100°C, such as 60°C, 70°C, 80°C, 100°C, etc.

[0067] Optionally, the second mixing time is 5-80 min, for example, 5 min, 20 min, 40 min, 60 min, 80 min, etc.

[0068] A third aspect of the embodiments of the present application provides application of the curing composition described in the first aspect in protecting the blue film on the front side of a solar cell.

[0069] The refractive index of the curing composition of the present application is 1.54-1.68, which forms a gradient difference with the refractive index of the photovoltaic film (1.4-1.5) and the refractive index of the silicon nitride layer on the surface of the solar cell (1.8-2.2), and forms a light-trapping structure to improve the light utilization rate of the photovoltaic module. In addition, the light transmittance of the curing composition is as high as 92.5%, which is much higher than the light transmittance of the existing blue film protective glue. Therefore, the curing composition of the present application is particularly suitable for the protection of the blue film on the front of the solar cell.

[0070] In some embodiments, a layer of glue is applied on the blue film on the front of the cell according to a certain pattern according to the cell pattern. After printing, the cell enters a UV curing box and is cured to obtain a cell with a printed curing composition. Figure 1 The cell 3 is coated with a curing composition 2 and an adhesive film layer 1. The curing composition 2 can enhance the protection of the cell after UV curing.

[0071] Optionally, the curable composition is applied by screen printing, dot printing, coating or sputtering.

[0072] Optionally, the curing is performed by ultraviolet light irradiation curing, and the ultraviolet light conditions include a wavelength of 300-400nm, such as 300nm, 340nm, 365nm, 400nm, etc. Intensity 2000-4000mj / cm 2 , for example 2000mj / cm 2 、3000mj / cm 2 、4000mj / cm 2 wait.

[0073] Optionally, the curing time is 1-20 seconds.

[0074] Hereinafter, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. It should be noted that these exemplary embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.

[0075] Example 1 33 parts by weight of acrylic monomer (ethoxybisphenol A dimethacrylate), 1.5 parts by weight of photoinitiator (1-hydroxycyclohexyl phenyl ketone), 1 part by weight of coupling agent (γ-aminopropyltriethoxysilane), 2 parts by weight of mesoporous silica microspheres, 0.5 parts by weight of promoter (adhesion promoter HN1731), and 1 part by weight of stabilizer (stabilizer BSF123) were mixed evenly and put into a ball mill at a speed of 1200 r / min for 7 minutes to grind until the scraper fineness was ≤15 um to obtain a mixture.

[0076] The mixture was uniformly mixed with 100 parts by weight of an acrylate prepolymer (E51 epoxy diacrylate resin oligomer) on a watch glass, and after being completely dissolved by heating at 80° C. for 40 min, it was placed in a desiccator and protected from light until it was used for light curing.

[0077] The curing composition is coated with a layer of glue on the blue film on the front of the cell according to the cell pattern by screen printing. After printing, the cell enters the curing box under the ultraviolet light conditions of 365nm and 3000m 3 j / cm 2 The battery is cured under the condition of printing the insulating layer to obtain a battery cell.

[0078] Examples 2-20 and Comparative Examples 1-5 The cell glue coating was carried out in the same manner as in Example 1, except that the components of the curing composition and the weight of each component are shown in Table 1.

[0079] Table 1

[0080] The following tests were performed on the solar cells after curing the printed curable compositions obtained in the above examples and comparative examples. The results are shown in Table 2.

[0081] (1) Refractive index test method: The refractive index of the UV curable composition at a thickness of 50 μm was tested using an ellipsometer. (2) Transmittance test method: The UV curable composition is prepared into a 50 μm film and the transmittance at 380 nm-1100 nm is tested using an ultraviolet spectrophotometer (scanned once every 5 nm).

[0082] (3) Viscosity of the curing composition Test method: The uncured, well-stirred composition was tested using a Brookfield type rotational viscometer; (4) EQE quantum efficiency test of cells coated with 50 μm thickness Test method: EQE quantum efficiency of the cell at a wavelength of 300-1200nm.

[0083] Table 2

[0084] It can be seen from Table 1 above that by comparing Examples 1-20 with Comparative Examples 1-5, it can be obtained that the viscosity of the curing combination of Examples 1-20 is better, and the refractive index and light transmittance of the curing composition of Examples 1-20 after being coated on the cell and cured are both better, and the cell coated with the curing composition has a better EQE quantum efficiency of the cell at a wavelength of 300-1200nm. The acrylate prepolymer, acrylic monomer, silane coupling agent, initiator, promoter and stabilizer react with each other through free radical polymerization, and the photoinitiator is stimulated by external light energy to produce active free radicals, and the active free radicals trigger the chain growth reaction of the acrylate prepolymer, and the acrylic monomer connects the generated linear macromolecules to each other to form a cross-linked network structure, so that the curing composition has good yellowing resistance, wear resistance, suitable refractive index and high light transmittance, and is particularly suitable for the front blue film protection of solar cells.

[0085] Comparing Example 1 with Comparative Example 1, since Comparative Example 1 does not contain acrylic oligomer, it is difficult to obtain a curing composition with better performance, so the various properties of the curing composition are not shown.

[0086] Comparing Example 1 with Comparative Example 2, Comparative Example 2 does not contain an acrylic monomer, and the performance of the cured composition obtained is poor. This is because the acrylic monomer can connect the generated linear macromolecules to each other to form a cross-linked network structure, and Comparative Example 2 does not contain this component, resulting in poor performance of the cured composition.

[0087] Comparing Example 1 with Comparative Example 3, Comparative Example 3 does not contain a silane coupling agent, and the performance of the cured composition obtained is poor. This is because the silane coupling agent can be used to improve the bonding performance of the cured composition and enhance the mechanical properties of the cured composition, while Comparative Example 3 does not contain this component, resulting in poor performance of the cured composition.

[0088] Comparing Example 1 with Comparative Example 4, Comparative Example 4 does not contain an initiator, and the initiator is used to initiate the reaction of the components. When Comparative Example 4 does not contain this component, the reaction of the components to form a cured composition is slow or even does not occur, so the various properties of the cured composition are not shown.

[0089] Comparing Example 1 with Comparative Example 5, Comparative Example 5 does not contain an accelerator, and the performance of the cured composition obtained is poor.

[0090] Comparing Example 1 with Example 19, Example 19 does not contain a stabilizer, and the performance of the cured composition obtained is poor.

[0091] Comparing Example 1 and Example 20, Example 20 does not contain silica filler, and the performance of the cured composition obtained is poor. This is because silica can improve the heat cycle resistance of the cured composition. Comparative Example 7 does not contain this component, and the performance of the cured composition obtained is poor.

[0092] It should also be noted that the "some embodiments", "other embodiments", "embodiments", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Furthermore, when a specific feature, structure or characteristic is described in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.

[0093] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0094] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A curing composition, characterized in that include: Acrylate prepolymer, acrylic monomer, silane coupling agent and initiator, With respect to 100 parts by weight of the acrylic ester prepolymer, the acrylic monomer is 25-40 parts by weight, the silane coupling agent is 0.5-1.5 parts by weight, and the initiator is 1-3 parts by weight.

2. The curing composition according to claim 1, characterized in that The invention also comprises an accelerator and a stabilizer. With respect to 100 parts by weight of the acrylic ester prepolymer, the accelerator is in an amount of 0.5-1.5 parts by weight, and the stabilizer is in an amount of 0.5-1.5 parts by weight.

3. The curing composition according to claim 1 or 2, characterized in that The acrylate prepolymer includes epoxy acrylate resin oligomer.

4. The curing composition according to claim 1 or 2, characterized in that The acrylic monomer includes one or any combination of ethoxyphenol acrylate, ethoxybisphenol A dimethacrylate, o-phenylphenoxyethyl acrylate, 3-ethoxyethyl acrylate, and biphenylmethanol acrylate.

5. The curing composition according to claim 1 or 2, characterized in that The initiator includes 1-hydroxycyclohexyl phenyl ketone and / or phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide.

6. The curing composition according to claim 1 or 2, characterized in that The silane coupling agent includes one or any combination of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

7. The curing composition according to claim 1 or 2, characterized in that The curing composition further comprises a filler, wherein the filler comprises one or any combination of silicon dioxide, diatomaceous earth, calcium carbonate, and talc; And / or, in the curing composition, the filler is 1.5-3 parts by weight relative to 100 parts by weight of the acrylate prepolymer.

8. The curing composition according to claim 7, characterized in that The silicon dioxide is porous silicon dioxide, the diameter of the porous silicon dioxide is 1-5 μm, and the pore size of the porous silicon dioxide is 0.3-3 μm.

9. The curing composition according to any one of claims 1 or 2, characterized in that The viscosity of the curing composition is 120-150 dPa.s.

10. The curing composition according to any one of claims 1 or 2, characterized in that The refractive index of the curing composition is 1.54-1.

68.

11. The curing composition according to any one of claims 1 or 2, characterized in that The light transmittance of the cured composition is at least 92.5%.

12. A method for preparing the curing composition according to any one of claims 1 to 11, characterized in that: The following steps are involved: The acrylic monomer, the silane coupling agent, the initiator, the accelerator and the stabilizer are first mixed and ball-milled to obtain a mixture; The mixture and the acrylic prepolymer are second mixed to obtain a curing composition.

13. The preparation method according to claim 12, characterized in that: The ball milling satisfies one or any combination of the following conditions: Speed: 1000r / min-1500r / min; Time is 5-10min; The particle size of the mixture is not greater than 15 μm.

14. The preparation method according to claim 13, characterized in that: The temperature of the second mixing is 60-100° C., and the time of the second mixing is 5-80 min.

15. Use of the curing composition according to any one of claims 1 to 11, characterized in that: The application includes application of the cured composition in protecting the blue film on the front side of a solar cell.